2007
DOI: 10.1111/j.1469-7610.2007.01755.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic physical illness and mental health in children. Results from a large‐scale population study

Abstract: Children with CI in the general population are at increased risk of behavioural and emotional problems and psychiatric disorders. Given its high sensitivity and specificity the SDQ might work well as a screening instrument for behaviour/emotional problems and psychiatric disorder in children with CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
131
2
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(165 citation statements)
references
References 27 publications
19
131
2
13
Order By: Relevance
“…where available. It has been highlighted that there is a significant lack of case controlled design and absence of observational data in looking at psychosocial outcomes following childhood stroke [14]. There is also a need for a qualitative approach to understand the perspectives of children and parents following childhood stroke [3,55] Several studies reported multiple papers from the same sample of children with stroke [17, Several of the larger outcome studies had a strong neurological focus [16,2] In studies that adopt a purely medical approach to outcome, children with mild residual physical disabilities are generally grouped in the 'good' outcome category.…”
Section: Predictors Of Hrqolmentioning
confidence: 99%
See 1 more Smart Citation
“…where available. It has been highlighted that there is a significant lack of case controlled design and absence of observational data in looking at psychosocial outcomes following childhood stroke [14]. There is also a need for a qualitative approach to understand the perspectives of children and parents following childhood stroke [3,55] Several studies reported multiple papers from the same sample of children with stroke [17, Several of the larger outcome studies had a strong neurological focus [16,2] In studies that adopt a purely medical approach to outcome, children with mild residual physical disabilities are generally grouped in the 'good' outcome category.…”
Section: Predictors Of Hrqolmentioning
confidence: 99%
“…Evidence from the wider paediatric literature suggests that children and young people living with disabilities, neurological or chronic health conditions may be at a significantly greater risk for behavioural and emotional adjustment problems and lower quality of life compared to those without disabilities [14,15]. There has been some emerging evidence into the broader impact of experiencing a stroke on a child's well-being, cognition, communication, behaviour and emotions, indicating that the long-term difficulties are far more wide-ranging than physical and neurological alone [12,13,16,3,17].…”
Section: Introductionmentioning
confidence: 99%
“…We are increasingly aware that emotional and behavioural problems occur in children with chronic illness and up to 20 % of children attending a variety of paediatric outpatient clinics had a probable psychiatric disorder [21,22]. Thirty per cent of 44 patients aged 9-18 years with CKD met the criteria for depression, which was more frequent in those with longstanding disease [23].…”
Section: Introductionmentioning
confidence: 99%
“…The participants reported helplessness, weakness and over sensitivity as their characteristics, which is consistent with the results of previous studies. Research show that chronically ill children often experience themselves as sensitive and dependent and that they have a perception of a lack of control [29][30][31]. Such experience of oneself is realistic in certain circumstances.…”
Section: Discussionmentioning
confidence: 99%